Correlation between Chest Radiograph and Lung Ultrasound with Clinical Appearance in Hyaline Membrane Disease Patients - Wa Ode Zerbarani; Sri Asriani; Mirna Muis; Ema Alasir (MEDULA (JURNAL ILMIAH FAKULTAS KEDOKTERAN UNIVERSITAS HALU OLEO), 2022)
ABSTRACT Background: Hyaline membrane disease (HMD) is a respiratory distress disease in premature infants due to surfactant deficiency. The combination of clinical, laboratory and radiological features makes it easy to quickly, precisely & accurately establish HMD which is important for early therapy in preventing death. Purpose: Knowing the suitability between chest X-ray & Thorax ultrasound with the clinical picture in HMD patients. Methods: This study is an observational study with a cross sectional method conducted in the radiology & NICU section of Dr. Wahidin Sudirohusodo Makassar from August 2021 to January  2022.  Sampling  was  done  by  consecutive  sampling.  The  researcher  performed  a  thorax ultrasound & assessed the chest x-ray. The results were verified by two pediatric radiology consultants. Results: The largest sample was in neonates at 34 weeks of gestation, 8 samples (21.1%), sex with 25 samples (65.8%), the highest birth weight between 1000-2000 grams 32 samples (84.2%) , the most preterm etiology was due to severe preeclampsia in 13 samples (34.2%), the most deliveries were by cesarean section 34 samples (89.4%), the highest APGAR Score was in moderate degree 25 samples (65.8%), the highest O2 saturation was between 90 -94%, namely 24 samples (63.2%), the most down scores were moderate degrees 15 samples (39.5%), HMD degrees based on chest radiographs were mostly grade II 25 samples (65.8%), HMD degrees based on thorax ultrasound the most in the moderate degree 19 samples (50%).Conclusion: Ultrasound is considered as the radiological modality of choice because it is safe, inexpensive, easy & sensitive to assess respiratory distress in neonates but is influenced by the operator's ability to apply it.Keywords: hyaline membrane disease, down score, chest radiograph, lung ultrasound